Association of endometriosis with asthma: a study of the NHANES database in 1999-2006 - Guangxin Pan; Pei Zhang; Sha Li; Lanlan Cao; Changqun Yang (BMC, 2024)
Abstract Objective Asthma is a chronic inflammatory disease of the airways with a gender differences in the prevalence after puberty. Recent studies have reported a relationship between asthma and endometriosis, possibly related to the immune response mechanisms, but the evidences are limited and inconsistent. Herein, this research aimed to investigate the association of endometriosis with asthma based on the representative population in the United States (U.S.) to provide some reference for further exploration on mechanism of gender difference in asthma. Methods In this cross-sectional study, data of women aged ≥ 20 years old were extracted from the National Health and Nutrition Examination Survey (NHANES) database in 1999-2006. Weighted univariate and multivariate logistic regression analyses were utilized to explore the association of endometriosis with asthma. The multivariate models adjusted for covariates including age, race, education level, marital status, poverty income ratio (PIR), body mass index (BMI), waist circumference, smoking, estrogen and progesterone hormones use, uterine fibroids, at least one ovary removed, and birth control pills intake. The evaluation indexes were odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup analyses of age, race, BMI, and pregnancy history were also performed. Results Among 5,556 eligible women, 782 had asthma, and 380 had endometriosis. The average age of participants was 37.19 years old, and more than half of them were non-Hispanic White (68.44%). After adjusting for covariates, endometriosis was associated with higher odds of asthma compared with non-endometriosis [OR = 1.48, 95%CI: (1.10-1.99)]. This relationship was also found in 40-49 years old [OR = 2.26, 95%CI: (1.21-4.23)], BMI of 25-29.9 kg/m2 [OR = 2.87, 95%CI: (1.52-5.44)], and pregnancy history [OR = 1.44, 95%CI: (1.01-2.06)] subgroups. Conclusion Endometriosis had a positive association with asthma in adult women. Females aged 40-49 years old, with BMI of 25-29.9 kg/m2 and had a history of pregnancy should take care about monitoring endometriosis to reduce the potential risk of asthma. Further studies are still needed to clarify the causal association between endometriosis and asthma.